ЄДИНА МОДЕЛЬ СИСТЕМИ ПЛАНУВАННЯ І УПРАВЛІННЯ НАВЧАЛЬНОЮ РОБОТОЮ СТУДЕНТІВ (Педагогіка вищої та середньої школи, 2008)
In the article the done attempt to define going near creation of model of some subsystems of educational process, namely management educational work of students. In quality an entrance a parameter take time which is outlaid by students on the different types of educational work.